A multi-layered biomimetic gradient structure rotator cuff patch and a method of making the same

CN117838932BActive Publication Date: 2026-10-27SHANGHAI UNIV OF ENG SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311803014.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-27
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

不可降解合成补片一般具有强大的抗拉强度,但存在诱导潜在的炎症反应、通常缺乏生物活性、不利于细胞粘附和组织再生并阻碍正常的肩袖生长修复过程的缺点

Benefits of technology

[0028]1.天然高分子材料具有良好的生物相容性,合成高分子材料具有优异的力学性能,两者相结合,既解决合成高分子材料肩袖补片术后的排异反应,又解决天然高分子材料肩袖补片的力学性能不足问题,同时梯度浓度的促成骨材料模拟肩袖腱-骨界面的结构促进成骨。本发明选用能够诱导成肌腱的天然高分子材料促进肌腱再生,中间少量的促成骨材料诱导矿化纤维软骨的形成,底层中较多的促成骨材料诱导干细胞的成骨分化,通过控制促成骨材料量的变化模拟腱骨界面的一个过渡结构,从而实现腱骨界面再生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117838932B_ABST
    Figure CN117838932B_ABST
Patent Text Reader

Abstract

The application discloses a kind of multilayer biomimetic gradient structure shoulder sleeve patch and preparation method thereof, the shoulder sleeve patch is by the multilayer three-dimensional structure of different concentration nanofiber membrane stacking, nanofiber membrane is invariable in radial concentration, longitudinal according to the concentration of osteogenic material gradient change is divided into four sections, simulate tendon-bone interface histological characteristics in biological performance aspect;Each section contains multilayer nanofiber membrane, and each layer nanofiber membrane is invariable in radial concentration, forms the nanofiber membrane stacking composite nanofiber scaffold of multilayer biomimetic gradient structure.The multilayer biomimetic gradient structure shoulder sleeve patch of the application has higher porosity and water absorption rate, provides sufficient adhesion site for cell growth, has hierarchical mechanical properties and tissue induction characteristics, while matching the repair needs of different parts, realizes the precision treatment of shoulder sleeve tendon-bone interface regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical materials technology, specifically relating to a multi-layer biomimetic gradient structure rotator cuff patch and its preparation method. Background Technology

[0002] Rotator cuff tears are a common condition that can lead to chronic shoulder pain and functional impairment, significantly reducing patients' overall quality of life. Rotator cuff tears exceeding 5 cm or involving the rupture of two or more tendons are termed giant rotator cuff tears, which typically require surgical treatment. Re-tearing after surgery is a major concern following giant rotator cuff repair. Rotator cuff patches provide a framework for cell infiltration and growth, and reduce stress on the repair site, thereby promoting tissue healing and minimizing the occurrence of re-tears. With the continuous advancement of tissue engineering technology, the development of novel rotator cuff patches has gradually become a research hotspot in the treatment of giant rotator cuff tears.

[0003] Rotator cuff repair surgery is prone to secondary tears because the rotator cuff is located at the tendon-bone junction, and the reconstruction of both soft and hard tissues has always been a medical challenge. With the development of tissue engineering, the gradient structure of the tendon-bone interface has been discovered. Biomimetic gradient structure rotator cuff patches can improve the mechanical properties of the rotator cuff tissue after repair surgery and enhance the intrinsic healing potential of the tendon-bone interface, thereby increasing the success rate of rotator cuff repair surgery. Currently, clinically used patches can be divided into two main categories: synthetic material patches and biomaterial patches. Synthetic material rotator cuff patches can be further subdivided into non-degradable synthetic patches and biodegradable synthetic patches. Non-degradable synthetic patches generally have high tensile strength, but they have drawbacks such as inducing potential inflammatory responses, often lacking bioactivity, hindering cell adhesion and tissue regeneration, and impeding the normal rotator cuff growth and repair process. Biodegradable synthetic patches can provide non-permanent attachment points for rotator cuff self-repair and can be absorbed within an appropriate time, but their mechanical strength is generally poor. Biomaterial patches are tissue grafts derived from biological sources and can be categorized into autologous patches, allogeneic patches, and xenogeneic patches. They typically suffer from drawbacks such as relatively unstable mechanical properties, transplant-related chronic immune responses, or foreign body reactions. In short, most rotator cuff patches currently lack sufficient bioactivity to achieve effective and rapid healing. Furthermore, while traditional rotator cuff patches can temporarily replace tissue, they cannot restore the physiological stress transmission pattern of the tendon-bone interface (TBI), easily leading to delayed healing or even secondary tears.

[0004] It is generally believed that the high recurrence rate of rotator cuff repair surgery is related to the difficulty of restoring the unique structure of the tendon-bone interface using traditional treatment strategies. The tendon-bone interface is the transitional region between soft and hard tissues, and can be layered into bone tissue, mineralized fibrocartilage, non-mineralized fibrocartilage, and tendon tissue. From tendon to bone, collagen fibers gradually decrease while mineral content gradually increases, forming a unique transitional structure. This structure facilitates the uniform transfer of stress from soft tissue to hard tissue, preventing stress concentration-mediated tears. Therefore, much research has focused on developing various biomaterials to promote tendon-bone healing and enable in-situ regeneration of autologous living tissue from damaged rotator cuffs. This regenerated tissue is believed to mimic the natural structure and function of the original healthy tissue and possess long-term viability. Summary of the Invention

[0005] To address the aforementioned shortcomings of existing technologies, the main objective of this invention is to provide a multi-layered biomimetic gradient structure rotator cuff patch. This novel biomimetic gradient rotator cuff patch simulates the transition structure of the tendon-bone interface, enhancing the mechanical properties of the rotator cuff tissue after rotator cuff repair surgery. Simultaneously, it can induce regeneration of the rotator cuff tendon-bone interface, improve tissue healing ability, and thus increase the therapeutic benefits of rotator cuff injury repair surgery.

[0006] Another objective of this invention is to provide a method for preparing the multi-layered biomimetic gradient structure rotator cuff patch, comprising different concentrations of inducing materials that induce cell differentiation in different ways, thereby achieving the formation of a gradient structure at the rotator cuff tendon-bone interface.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] This invention provides a multi-layered biomimetic gradient structure rotator cuff patch, which is composed of layers of nanofiber membranes with different concentrations stacked together to form a multi-layered three-dimensional structure resembling a "thousand-layer cake". The nanofiber membranes are processed from one or more selected from natural polymer materials, synthetic polymer materials, and osteogenic materials. The concentration remains constant radially, while longitudinally it varies in a gradient according to the concentration of the osteogenic material, divided into four segments. In terms of biological performance, it simulates the histological characteristics of the tendon-bone interface; wherein:

[0009] Each segment contains multiple nanofiber membranes, with the concentration of bone-promoting material varying from 0% in the first layer of the first segment to 4.0% in the last layer of the fourth segment. The concentration of each layer changes in a gradient, while the concentration of each nanofiber membrane remains constant in the radial direction, forming a multi-layered biomimetic gradient structure of nanofiber membrane stacked composite nanofiber scaffold, namely a four-segment rotator cuff patch.

[0010] As a preferred embodiment, the first-segment rotator cuff patch simulates the tendon tissue at the rotator cuff tendon-bone interface in terms of biocompatibility; the second-segment rotator cuff patch simulates the unmineralized fibrocartilage tissue at the rotator cuff tendon-bone interface in terms of biocompatibility; the third-segment rotator cuff patch simulates the mineralized fibrocartilage tissue at the rotator cuff tendon-bone interface in terms of biocompatibility; and the fourth-segment rotator cuff patch simulates the bone tissue at the rotator cuff tendon-bone interface in terms of biocompatibility.

[0011] Preferably, the rotator cuff patch is connected sequentially from the first segment to the fourth segment to form a segment that promotes tendon regeneration, a segment that promotes the formation of unmineralized fibrocartilage, a segment that promotes the formation of mineralized fibrocartilage, and a segment that promotes bone formation.

[0012] Preferably, the multi-layer biomimetic gradient structure rotator cuff patch has the side close to the tendon tissue as the first layer and the side close to the bone as the last layer; the first layer is a natural polymer material, the second layer is a combination of natural and synthetic polymer materials, and the third to the last layer is a combination of natural polymer materials, synthetic polymer materials, and a gradient concentration of osteogenic materials.

[0013] Preferably, the processing technology of the nanofiber membrane is selected from one or more of casting, thermally induced phase separation, electrospinning, 3D printing, and weaving, and more preferably electrospinning.

[0014] Preferably, the three-dimensional structure of the multi-layer biomimetic gradient structure shoulder and sleeve patch is selected from one or more of cubes, cuboids, cylinders, and polygons.

[0015] Preferably, each segment of the multi-layer biomimetic gradient structure shoulder and sleeve patch comprises at least one layer of nanofiber membrane, with a single layer thickness of 0.1 to 1.0 mm and / or a distance between layers of 0 to 0.01 mm; and / or the total thickness of the multi-layer biomimetic gradient structure shoulder and sleeve patch is 0.5 to 3.0 mm.

[0016] Preferably, the concentration of the osteogenic material is 0% to 4.0%, and the concentration difference of the osteogenic material between layers is 0.2% to 1.0%, and it is selected from one or more osteogenic drugs, osteogenic growth factors and inorganic osteogenic materials.

[0017] More preferably, the concentration distribution of the bone-promoting material is as follows: the concentration of the first-stage and second-stage bone-promoting materials is 0%; the concentration of the third-stage bone-promoting material is 1% to 1.5%; and the concentration of the fourth-stage bone-promoting material is 1.5% to 4.0%.

[0018] Preferably, the concentration ratio of the synthetic polymer material to the natural polymer material is 1:4 to 4:1.

[0019] Preferably, the synthetic polymer material is selected from one or more of PLA, PGA, PGCL, PLGA, PCL, and PEG.

[0020] Preferably, the natural polymer material is selected from one or more of collagen, gelatin, hyaluronic acid, silk fibroin, chitosan, and alginate.

[0021] This invention also provides a method for preparing the multi-layer biomimetic gradient structure shoulder and sleeve patch, which is prepared by electrospinning and includes the following steps:

[0022] Step 1: Dissolve the synthetic polymer material in an organic solvent, then add the natural polymer material, and finally add the osteogenic material to prepare solutions with different concentration gradients;

[0023] Step 2: Turn on the electrospinning receiving device, set the electrospinning process parameters, use a syringe to draw up the solution from Step 1, and perform electrospinning in sequence according to the gradient concentration to obtain a layered gradient structure of nanofiber membrane stacked composite nanofiber scaffold.

[0024] Step 3: Place the prepared composite nanofiber scaffold in a fume hood for ventilation until the organic solvent evaporates completely.

[0025] Preferably, the electrospinning process parameters include: a positive pressure of 5.5 kW, a negative pressure of 1.3 kW, a feed speed of 0.8 mm / min, and a receiving distance of 10–20 cm.

[0026] In the multi-layered biomimetic gradient structure rotator cuff patch of this invention, the scaffold mimics the histological characteristics of tendons, unmineralized fibrocartilage, mineralized fibrocartilage, and bone gradient structures in terms of structure and bioperformance, resulting in a four-segment artificial rotator cuff patch that promotes rotator cuff tendon-bone interface regeneration. The rotator cuff patch resembles a multi-layered three-dimensional structure resembling a "thousand-layer cake," with layers stacked one on top of the other. Each segment contains one or more layers. In the longitudinal direction, the concentration of bone-promoting material varies gradient between layers, from 0% in the first layer of the first segment to 4.0% in the last layer of the fourth segment. This invention employs a multi-layered biomimetic gradient structure. During rotator cuff repair, the first segment of the rotator cuff patch connects to the tendon tissue, while the fourth segment connects to the bone tissue. These segments are fixed to the tendon-bone interface using biodegradable screws, promoting the growth and repair of both tendon and bone tissues and effectively establishing the tendon-bone interface insertion point. The multi-layered biomimetic gradient structure rotator cuff patch has high porosity and water absorption, providing ample adhesion sites for cell growth. Furthermore, the fabricated multi-layered biomimetic gradient structure rotator cuff patch possesses graded mechanical and tissue-inducing properties. Simultaneously, the multi-layered structural design matches the repair needs of different areas, achieving precise treatment for rotator cuff tendon-bone interface regeneration.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. Natural polymer materials possess excellent biocompatibility, while synthetic polymer materials exhibit superior mechanical properties. Combining the two addresses both the postoperative rejection reaction of synthetic polymer rotator cuff patches and the insufficient mechanical properties of natural polymer rotator cuff patches. Simultaneously, gradient concentrations of osteogenic materials mimic the structure of the rotator cuff tendon-bone interface, promoting osteogenesis. This invention selects natural polymer materials capable of inducing tendon formation to promote tendon regeneration, a small amount of osteogenic material in the middle to induce the formation of mineralized fibrocartilage, and a larger amount of osteogenic material in the bottom layer to induce osteogenic differentiation of stem cells. By controlling the variation in the amount of osteogenic material, a transitional structure at the tendon-bone interface is simulated, thereby achieving tendon-bone interface regeneration.

[0029] 2. The present invention provides a simple method for preparing a multi-layer biomimetic gradient structure rotator cuff patch. The resulting four-segment artificial rotator cuff patch has graded mechanical properties and tissue induction properties. At the same time, the multi-layer structure design matches the repair needs of different parts, realizing precise treatment for rotator cuff tendon-bone interface regeneration.

[0030] 3. While traditional rotator cuff patches can temporarily replace tissue, they cannot restore the physiological stress transmission pattern at the tendon-bone interface, easily leading to delayed healing or even secondary tears. This invention proposes a novel biomimetic gradient rotator cuff patch based on a biomimetic strategy, simulating the transition structure of the tendon-bone interface. Compared to conventional patches with a uniform structure, this patch has enhanced tensile and fatigue resistance. Applied to the rotator cuff tendon-bone interface, the first segment connects to the tendon, and the fourth segment connects to the bone. It is fixed to the tendon-bone interface with biodegradable screws, which is expected to prevent re-tears after rotator cuff repair surgery.

[0031] 4. Currently, most rotator cuff patches lack sufficient bioactivity and cannot achieve effective and rapid healing. This invention proposes a novel rotator cuff patch with an MBGs concentration gradient structure, which can induce the adhesion, proliferation, and differentiation of tendon and bone tissues on different surfaces of the patch, thereby effectively accelerating the repair process of rotator cuff injuries. It has broad clinical application prospects and is expected to improve the treatment benefits of rotator cuff injury repair surgery. Attached Figure Description

[0032] Figure 1 The mechanical properties of the uniform patch (SPM) and gradient patch (SPGM) in the examples are as follows: a: Stress loss rate of each patch group after 5 and 10 tensile cycles, respectively; b: Stress-strain curves of each patch group; c: Quantitative analysis of the maximum tensile stress and maximum strain of each patch group.

[0033] Figure 2The following is a co-culture experiment of the patch front and human fibroblasts (HSF-1) in the example: a: cell viability of HSF-1 on days 1, 3 and 5 of co-culture; b: absorbance values ​​at 450 nm on days 1, 3 and 5 of co-culture for each group.

[0034] Figure 3 The following is a co-culture experiment of the back of the patch and mouse osteoblasts (MC3T3-E1) in the example: a: cell viability of MC3T3-E1 on days 1, 3 and 5 of co-culture; b: total protein content of cells on days 3 and 5 of co-culture; c: alkaline phosphatase (ALP) activity of cells on day 5 of co-culture.

[0035] Figure 4 This is a schematic diagram illustrating the preparation of a shoulder and sleeve patch support with an MBGs concentration gradient by layer-by-layer electrospinning in the embodiment. Detailed Implementation

[0036] To make the technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0037] Example 1

[0038] (1) Preparation of spinning solution

[0039] First, the biodegradable synthetic polymer material is dissolved in an organic solvent, then natural polymer material is added. The concentration ratio of synthetic polymer material to natural polymer material is 1:1. Finally, osteogenic material is added in a certain proportion to prepare solutions with different concentration gradients.

[0040] (2) Spinning device

[0041] Fix aluminum foil onto the receiving device, and use a 2.5mL syringe to draw 2mL of solution each time, and spin the solution sequentially according to the gradient concentration.

[0042] (3) Setting process parameters

[0043] Voltage: Positive voltage: 5.5kw, Negative voltage: 1.3kw.

[0044] Propulsion speed: 0.8 mm / min.

[0045] Receiving distance: 10-20cm.

[0046] (4) Place the prepared composite nanofiber scaffold in a fume hood for two days to allow the solvent to evaporate.

[0047] Example 2

[0048] (1) Preparation of spinning solution

[0049] First, the biodegradable synthetic polymer material is dissolved in an organic solvent, then natural polymer material is added. The concentration ratio of synthetic polymer material to natural polymer material is 3:1. Finally, osteogenic material is added in a certain proportion to prepare solutions with different concentration gradients.

[0050] (2) Spinning device

[0051] Fix aluminum foil onto the receiving device, and use a 2.5mL syringe to draw 1mL of solution, and spin the fibers sequentially according to the gradient concentration.

[0052] (3) Setting process parameters

[0053] Voltage: Positive voltage: 4.5kw, Negative voltage: 1.3kw.

[0054] Propulsion speed: 1.0 mm / min.

[0055] Receiving distance: 15-20cm.

[0056] (4) Place the prepared composite nanofiber scaffold in a fume hood to allow the organic solvent to evaporate completely.

[0057] Example 3

[0058] The mechanical properties of the samples prepared in Examples 1 and 2 were tested.

[0059] Stretching Cycle

[0060] The spun composite nanofiber scaffold was cut into rectangles 50 mm long and 10 mm wide. Tensile tests were conducted on it at room temperature using a mechanical testing instrument at a tensile rate of 1.0 mm / min. The tensile cycle test was performed by stretching to 30% strain and then restoring the original shape, and the stretching was repeated 10 times.

[0061] Tension test

[0062] The spun composite nanofiber scaffold was cut into rectangles 50 mm long and 10 mm wide, and subjected to tensile testing at room temperature using a mechanical testing instrument. The tensile rate was 1.0 mm / min, and the force was greater than or equal to 180 N.

[0063] Example 4

[0064] Cellular experiments were performed on the samples prepared in Examples 1 and 2, as follows:

[0065] HSF-1 was cultured in complete medium (DMEM containing 1% penicillin-streptomycin and 10% fetal bovine serum). Prior to cell culture, SP, SPM, and SPGM scaffolds were divided into 14 mm diameter discs, face up, and placed in 24-well plates. Each scaffold was then covered with a sterile stainless steel ring. Each sample was immersed in 75% ethanol for 2 hours, followed by three washes with PBS. After 8 hours of UV irradiation, the samples were incubated overnight in growth medium. HSF-1 was then evenly seeded into 24-well plates (1.5 × 10⁻⁶ wells). 4 The culture medium was changed every other day in cells / well. After 1, 3, and 5 days of culture, the OD value was measured at 450 nm. The cell viability was determined by the following formula: Cell viability (%) = (OD1 - OD2) / (OD0 - OD2) × 100%, where OD1 is the OD value of the experimental group, OD0 is the OD value of the control group, and OD2 is the OD value of CCK-8.

[0066] MC3T3-E1 was cultured in α-MEM containing 1% penicillin-streptomycin and 10% fetal bovine serum. Samples were prepared as described above, with the back side facing up, and placed in 24-well plates. After sterilization as described above, MC3T3-E1 was evenly inoculated into 24-well plates (4.0 × 10⁻⁶). 4 Cells were cultured in wells (cells / well). Total cellular protein levels were quantified using a BCA assay kit on days 3 and 5. OD values ​​were measured at 450 nm after days 1, 3, and 5, and cell viability was calculated as described above. Additionally, ALP activity was assessed using an assay kit on day 5, according to the manufacturer's instructions.

[0067] result

[0068] During the repair process, the rotator cuff tissue is greatly affected by external stress. Comprehensive biomechanical testing was performed on the SPM and SPGM, and the results are as follows: Figure 1 As shown. From Figure 1 As can be seen from this, after 10 cycles of testing, the total stress loss rate of SPGM was less than 20%, thus exhibiting better fatigue resistance. The pressure loss in each group was less than 37%, and there was no statistically significant difference in pressure loss among the groups. Figure 1 The tensile stress-strain curves in b and 1c show that, compared to the SPM scaffold, the SPGM exhibits reduced stress and increased elongation at break, indicating that the gradient structure of the patch effectively avoids stress concentration. In short, the mechanical properties of the prepared SPGM meet the requirements for rotator cuff tissue repair and regeneration.

[0069] Further evaluation of the HSF-1 proliferation behavior at the tip of the nanofiber scaffold was conducted through co-culture experiments of the patch front and HSF-1. The results are as follows: Figure 2 As shown. In all groups, the number of HSF-1 increased with increasing culture time. Figure 2 b). Importantly, HSF-1 showed higher cell proliferation rates in both the SPM and SPGM groups compared to SP without MBGs. Figure 2 a) This may be due to the promoting effect of MBGs on fibroblast adhesion and proliferation. In fact, MBGs can also promote the secretion of type I collagen and VEGF-type collagen by fibroblasts, which are crucial for tendon repair and regeneration.

[0070] Furthermore, the proliferative behavior and osteogenic differentiation potential of MC3T3-E1 located on the back of the nanofiber scaffold were evaluated through a co-culture experiment between the patch backside and MC3T3-E1. The results are as follows: Figure 2 As shown. After co-culturing for 1, 3, and 5 days, MC3T3-E1 exhibited better cell adhesion and proliferation behavior on the back side of SPM and SPGM, attributed to its relatively high concentration of MBGs and the provision of more suitable mechanical cues for cell growth. Figure 3 a). Quantitative analysis of total cellular protein also showed similar results ( Figure 3 b). ALP activity is a recognized indicator of osteoblast differentiation, such as... Figure 3 As shown in c, MC3T3-E1 showed a significantly higher degree of osteogenic differentiation in the SPM and SPGM groups than in the other two groups, and the SPGM group had the highest ALP activity, confirming that the MBG gradient in the SPGM nanofiber scaffold can more effectively promote osteogenic differentiation.

[0071] like Figure 4 As shown, rotator cuff patches with MBG concentration gradients were prepared by layer-by-layer electrospinning for the repair and regeneration of the rotator cuff tendon-bone interface. Experimental results showed that the upper end of the SPGM (SF surface) scaffold could induce the adhesion and proliferation of HSF-1 cells, while the lower end of the SPGM (PGCL / SF / MBG-4.0) scaffold could promote the proliferation and osteogenic differentiation of MC3T3-E1 cells, providing a novel therapeutic strategy for rotator cuff tendon-bone interface repair.

[0072] The above description represents a preferred embodiment of the present invention, but the present invention should not be limited to the content disclosed in this embodiment. Therefore, any equivalent or modified versions made without departing from the spirit of the present invention fall within the scope of protection of the present invention.

Claims

1. A multi-layered biomimetic gradient structure shoulder and cuff patch, characterized in that, It is a multi-layered three-dimensional structure composed of stacked nanofiber membranes with varying concentrations. These nanofiber membranes are manufactured using one or more of a selection from natural polymers, synthetic polymers, and osteogenic materials. The concentration remains constant radially, while longitudinally it varies in a gradient according to the concentration of the osteogenic material, forming several segments. In terms of biological performance, it simulates the histological characteristics of the tendon-bone interface. Each segment contains at least one nanofiber membrane, and the concentration of each nanofiber membrane remains constant in the radial direction, while the concentration of bone-promoting material changes in the longitudinal direction to form a nanofiber membrane stacked composite nanofiber scaffold, thus obtaining the desired structure. The multi-layered biomimetic gradient structure rotator cuff patch is a four-segment design. The first segment of the rotator cuff patch simulates the tendon tissue at the rotator cuff tendon-bone interface in terms of biological performance. The second segment of the rotator cuff patch simulates the unmineralized fibrocartilage tissue at the rotator cuff tendon-bone interface in terms of biological performance. The third segment of the rotator cuff patch simulates the mineralized fibrocartilage tissue at the rotator cuff tendon-bone interface in terms of biological performance. The fourth segment of the rotator cuff patch simulates the bone tissue at the rotator cuff tendon-bone interface in terms of biological performance. The multi-layered biomimetic gradient structure rotator cuff patch has the side close to the tendon tissue as the first layer and the side close to the bone as the last layer; the first layer is a natural polymer material, the second layer is a combination of natural and synthetic polymer materials, and the third to the last layer consists of natural polymer materials, synthetic polymer materials, and a gradient concentration of osteogenic materials. The concentration of the osteogenic material is 0% to 4.0%, and the concentration difference of the osteogenic material between layers is 0.2% to 1.0%, and it is selected from one or more of osteogenic active drugs, osteogenic active growth factors and inorganic osteogenic materials; The concentration distribution of the bone-promoting material is as follows: the concentration of the first and second stage bone-promoting materials is 0%; the concentration of the third stage bone-promoting material is 1% to 1.5%; and the concentration of the fourth stage bone-promoting material is 1.5% to 4.0%.

2. The multi-layer biomimetic gradient structure shoulder and sleeve patch according to claim 1, characterized in that, The rotator cuff patch is connected sequentially from the first segment to the fourth segment, which are segments that promote tendon regeneration, promote the formation of unmineralized fibrocartilage, promote the formation of mineralized fibrocartilage, and promote bone formation.

3. The multi-layer biomimetic gradient structure shoulder and sleeve patch according to claim 1, characterized in that, The processing technology of the nanofiber membrane is selected from one or more of the following: casting, thermally induced phase separation, electrospinning, 3D printing, and weaving. And / or the multi-layered three-dimensional structure of the aforementioned multi-layered biomimetic gradient structure shoulder sleeve patch is selected from one or more of the following: cube, cuboid, cylinder, and polygon. And / or in the multilayer biomimetic gradient structure rotator cuff patch, the thickness of a single nanofiber membrane is 0.1~1.0 mm, and / or the distance between layers is 0~0.01 mm; and / or the total thickness of the multilayer biomimetic gradient structure rotator cuff patch is 0.5~3.0 mm.

4. The multi-layer biomimetic gradient structure shoulder and sleeve patch according to claim 1, characterized in that, The concentration ratio of the synthetic polymer material to the natural polymer material is 1:4 to 4:1; and / or the synthetic polymer material is selected from one or more of PLA, PGA, PGCL, PLGA, PCL, and PEG; and / or the natural polymer material is selected from one or more of collagen, gelatin, hyaluronic acid, silk fibroin, chitosan, and alginate.

5. The method for preparing the multi-layer biomimetic gradient structure rotator cuff patch according to any one of claims 1 to 4, characterized in that, Includes the following steps: Step 1: Dissolve the synthetic polymer material in an organic solvent, then add the natural polymer material, and finally add the osteogenic material to prepare solutions with different concentration gradients; Step 2: Turn on the electrospinning receiving device, set the electrospinning process parameters, use a syringe to draw up the solution from Step 1, and perform electrospinning in sequence according to the gradient concentration to obtain a layered gradient structure of nanofiber membrane stacked composite nanofiber scaffold. Step 3: Place the prepared composite nanofiber scaffold in a fume hood for ventilation until the organic solvent evaporates completely.

6. The method for preparing the multi-layer biomimetic gradient structure rotator cuff patch according to claim 5, characterized in that, The electrospinning process parameters include: positive pressure of 5.5 kW, negative pressure of 1.3 kW, feed speed of 0.8 mm / min, and receiving distance of 10~20 cm.

Citation Information

Patent Citations

  • Preparation method of biomimetic bone material containing graphene, hydroxyapatite and fibroin

    CN105169475A

  • Collagen in-situ mineralization scaffold for simulating bone matrix and preparation method of collagen in-situ mineralization scaffold

    CN116899021A